A dimeric fullerene derivative for efficient inverted planar perovskite solar cells with improved stability. Issue 16 (7th March 2017) - Tian, Chengbo; Kochiss, Kevin; Castro, Edison; Betancourt-Solis, German; Han, Hongwei; Echegoyen, Luis
Abstract : Efficiency and stability are improved in inverted planar perovskite solar cells by using D-C60 as electron transport material. Abstract : Fullerene derivatives can efficiently passivate the interfacial defects of perovskite layers to improve the performance of perovskite solar cells. In this work, a new dimeric fullerene derivative (D-C60 ) with two [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) units was designed, synthesized and applied as the electron transporting material (ETM) in perovskite solar cells (PSCs) taking advantage of its appropriate energy levels, relatively fast electron mobility, and easy solution processability compared to the widely used PC61 BM, D-C60 can efficiently passivate the trap states between the perovskite and fullerene layers, leading to improved electron extraction and overall photovoltaic performance. Devices based on D-C60 as the ETM achieved power conversion efficiencies (PCEs) of 16.6%, which is significantly higher than that observed with PC61 BM (14.7%). In addition, the more hydrophobic and compact D-C60 layer resulted in higher device stability than that with PC61 BM. These results show that covalently linked dimeric fullerene derivative can act as efficient electron transporting materials (ETMs) for high performance PSCs.